2020
DOI: 10.1016/j.fertnstert.2020.03.034
|View full text |Cite|
|
Sign up to set email alerts
|

Is there a correlation between paternal age and aneuploidy rate? An analysis of 3,118 embryos derived from young egg donors

Abstract: Objective: To investigate a possible correlation between chromosomal aberrations and paternal age, analyzing embryos derived from young oocyte donors, with available preimplantation genetic testing for aneuploidy results from day 5/6 trophectoderm biopsy obtained by next-generation sequencing for all 24 chromosomes. Design: Retrospective cohort study. Setting: Canadian fertility centre. Patient(s): A total of 3,118 embryos from 407 male patients, allocated into three paternal age groups: group A, %39 years (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Female age is a prominent factor affecting the outcome of ICSI-IVF [19,20]. However, male age had no signi cant effect on the rate of aneuploidy embryos [21]. The female age in this study ranged from 26 to 37, of which 16 were under 35 years old and 6 were over 35 years old.…”
Section: Discussionmentioning
confidence: 73%
“…Female age is a prominent factor affecting the outcome of ICSI-IVF [19,20]. However, male age had no signi cant effect on the rate of aneuploidy embryos [21]. The female age in this study ranged from 26 to 37, of which 16 were under 35 years old and 6 were over 35 years old.…”
Section: Discussionmentioning
confidence: 73%
“…As for single-gene perturbations, several genes have been suggested to be implicated in POI (Table 1), some of them located on the X-chromosome and others on autosomes [4,8,9]. 1 See the main text for the full name of each gene. Full review of the genes can be found in references [4,8,9].…”
Section: Primary Ovarian Insufficiencymentioning
confidence: 99%
“…The importance of issues related to ovarian aging has been increasing progressively over the past several decades since, increasingly, more couples in all developed countries choose to postpone parenthood to more advanced female ages [1]. This trend is associated with an increasing rate of aneuploidy in oocytes, causing chromosomal abnormalities in embryos resulting from natural conception, conventional in vitro fertilization (IVF), or intracytoplasmic sperm injection (ICSI) [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FINANCIAL SUPPORT: None. BACKGROUND: The literature suggests that advanced paternal age impacts embryo development and increases risk for embryonic genetic aberrations, although studies have reported conflicting results [1,2]. It is unclear whether this association translates into a clinically relevant impact on number of available euploid embryos.…”
Section: Referencesmentioning
confidence: 99%